2019
DOI: 10.1111/ijfs.14195
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil nanoemulsions: antibacterial activity in contaminated fruit juices

Abstract: Summary Many human acid tolerant bacterial and fungal pathogens can be transmitted through the consumption of the contaminated fruit juices. We aim to formulate essential oil nanoemulsions (basil, black seed, turmeric, clove & cinnamon), determine their ability to clear contamination by food borne bacterial pathogens from fruit juices. The antibacterial activity of the optimised formulations was tested in the fruit juices against bacterial pathogens causing gastrointestinal tract infections. The minimum bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Ocimium Basilicum L. known as purple basil (PB) is a member of the Lamiaceae family that has long been used for both seasoning to enhance the flavors of foods and remedies of variety of diseases as complementary and alternative medicine. Previous studies suggested that PB could have potential clinical applications for treating diseases related to cancer, allergy, inflammation, and infections against bacterial, fungal, and viral due to its naturally occurring food compositions rich in polyphenol, aromatic compounds, and essential oils (Franklyne et al., 2019; Torpol et al., 2019; Złotek et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ocimium Basilicum L. known as purple basil (PB) is a member of the Lamiaceae family that has long been used for both seasoning to enhance the flavors of foods and remedies of variety of diseases as complementary and alternative medicine. Previous studies suggested that PB could have potential clinical applications for treating diseases related to cancer, allergy, inflammation, and infections against bacterial, fungal, and viral due to its naturally occurring food compositions rich in polyphenol, aromatic compounds, and essential oils (Franklyne et al., 2019; Torpol et al., 2019; Złotek et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For P. aeruginosa , D. multicaule EO alone showed the least inhibitory effect and no significant difference was observed between the other treatments at 25°C ( p > .05). Franklyne, Iyer, Ebenazer, Mukherjee, and Chandrasekaran (2019) examined the antibacterial effect of turmeric, basil, clove, black seed, and cinnamon essential oils and their nanoemulsions in fruit juices. They reported that among the essential oils, clove, and cinnamon showed the highest antibacterial activity against the pathogenic bacteria and cinnamon oil emulsions maintained the sterility of fruit juices for 7 days at ambient temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoemulsions thus offer a new method of encapsulating sensitive molecules such as proteins, enzymes, phages in a nanoporous matrix. The confinement of bio-molecules within nanoemulsions causes a change in the surrounding a w (water activity) which imparts higher stability during storage period ( Franklyne et al, 2019 ). Such multiple emulsion formulations can act as a suitable housing system shielding the phage from inactivation from immune system, outer proteolytic enzymes while maintaining their structural and functional activity ( Balcão et al, 2014 ; Esteban et al, 2014 ; Sawant et al, 2017 ).…”
Section: Nanotechnology To the Rescuementioning
confidence: 99%